Prevalence and Type of Human Papillomavirus Infection in Thai Males with Anogenital Warts - Jiamton S. (2023)
Objective: Low-risk (LR) human papillomavirus (HPV) infection is a recognized cause of anogenital warts (AGW). LR-HPV 6 and 11 are the HPV types that were reported to be associated with AGW. However, data specific to the HPV types that associate with AGW in Thailand are scarce. Accordingly, this study aimed to determine the prevalence of HPV in patients with AGW, and to investigate for association between HPV types and AGW among Thai males attending the sexually transmitted disease clinic of Siriraj Hospital – Thailand’s largest national tertiary referral center. Materials and Methods: This prospective study was conducted at the Department of Dermatology, Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, Thailand during April 2017 to December 2019. Thai males with at least one AGW were included. AGW specimens were obtained, and HPV genotyping was performed at both the genital and perianal areas. Results: A total of 43 Thai male participants (mean age: 37.3±13.8 years; range: 19-72) with AGW were enrolled. The rate of HPV positive detection at the genital area and the perianal area was 86.0% and 72.1%, respectively. The most common HPV types at the genital area were HPV 6, followed by HPV 11. Alternatively, the most common HPV types at the perianal area were HPV 11, followed by HPV 6. Conclusion: The findings of this study suggest LR-HPV types 6 and 11 as the culprit pathogenic causes of AGW among males in Thailand. These findings further support and emphasize the importance of HPV vaccination for prophylaxis against both HPV and AGW.